Strategies for improving approximate Bayesian computation tests for synchronous diversification - Overcast, Isaac; Bagley, Justin C. [UNESP]; Hickerson, Michael J. (Biomed Central Ltd, 2017)
Background: Estimating the variability in isolation times across co-distributed taxon pairs that may have experienced the same allopatric isolating mechanism is a core goal of comparative phylogeography. The use of hierarchical Approximate Bayesian Computation (ABC) and coalescent models to infer temporal dynamics of lineage co-diversification has been a contentious topic in recent years. Key issues that remain unresolved include the choice of an appropriate prior on the number of co-divergence events (psi), as well as the optimal strategies for data summarization. Methods: Through simulation-based cross validation we explore the impact of the strategy for sorting summary statistics and the choice of prior on psi on the estimation of co-divergence variability. We also introduce a new setting (beta) that can potentially improve estimation of psi by enforcing a minimal temporal difference between pulses of co-divergence. We apply this new method to three empirical datasets: one dataset each of co-distributed taxon pairs of Panamanian frogs and freshwater fishes, and a large set of Neotropical butterfly sister-taxon pairs. Results: We demonstrate that the choice of prior on. has little impact on inference, but that sorting summary statistics yields substantially more reliable estimates of co-divergence variability despite violations of assumptions about exchangeability. We find the implementation of beta improves estimation of psi, with improvement being most dramatic given larger numbers of taxon pairs. We find equivocal support for synchronous co-divergence for both of the Panamanian groups, but we find considerable support for asynchronous divergence among the Neotropical butterflies. Conclusions: Our simulation experiments demonstrate that using sorted summary statistics results in improved estimates of the variability in divergence times, whereas the choice of hyperprior on psi has negligible effect. Additionally, we demonstrate that estimating the number of pulses of co-divergence across co-distributed taxon-pairs is improved by applying a flexible buffering regime over divergence times. This improves the correlation between. and the true variability in isolation times and allows for more meaningful interpretation of this hyperparameter. This will allow for more accurate identification of the number of temporally distinct pulses of co-divergence that generated the diversification pattern of a given regional assemblage of sister-taxon-pairs.
Keywords: Approximate Bayesian computation (ABC); Comparative phylogeography; Divergence times; Synchronous diversification